Pemberdayaan Masyarakat Melalui Wirausaha Pabrik Tempe di Kampung Cimanglid Kabupaten Tasikmalaya - Permata, Sahara Indah; Karwati, Lilis; Nurlaila (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
Indonesia still faces the problem of high unemployment, especially among teenagers. Empowerment through entrepreneurship is a solution by increasing skills, independence, and access to economic opportunities through simple and locally-based tempeh production. Cimanglid Village, Tasikmalaya, is affected by unemployment, so tempeh entrepreneurship is expected to be a real solution. This study aims to determine the approach to community empowerment. The research method used is qualitative with a descriptive approach. Data collection was carried out through observation, interviews, and documentation. The results of the study include the possibility of showing that tempeh businesses support economic growth through training, mentoring, and market access. Strengthening is carried out through technical guidance, capital assistance, and marketing strategies. Protection is reflected in waste management and increasing product competitiveness. Support comes from the government, academics, and the surrounding community. Business maintenance is carried out through routine evaluation, product innovation, and cooperation. Tempeh entrepreneurship has proven effective in creating a sustainable local economy. In conclusion, this empowerment improves economic welfare and creates financial independence for the people of Cimanglid Village, although they still face challenges such as limited capital, fluctuations in raw material prices, and market competition that require a more comprehensive strategy and ongoing support from various stakeholders